Physics and performance of the I-mode regime over an expanded operating space on Alcator C-Mod. (4th October 2017) - Hubbard, A.E.; Baek, S.-G.; Brunner, D.; Creely, A.J.; Cziegler, I.; Edlund, E.; Hughes, J.W.; LaBombard, B.; Lin, Y.; Liu, Z.; Marmar, E.S.; Reinke, M.L.; et al.
Abstract: New results on the I-mode regime of operation on the Alcator C-Mod tokamak are reported. This ELM-free regime features high energy confinement and a steep temperature pedestal, while particle confinement remains at L-mode levels, giving stationary density and avoiding impurity accumulation. I-mode has now been obtained over nearly all of the magnetic fields and currents possible in this high field tokamak ( I p 0.55–1.7 MA, B T 2.8–8 T) using a configuration with B × ∇ B drift away from the X -point. Results at 8 T confirm that the L–I power threshold varies only weakly with B T, and that the power range for I-mode increases with B T ; no 8 T discharges transitioned to H-mode. Parameter dependences of energy confinement are investigated. Core transport simulations are giving insight into the observed turbulence reduction, profile stiffness and confinement improvement. Pedestal models explain the observed stability to ELMs, and can simulate the observed weakly coherent mode. Conditions for I–H transitions have complex dependences on density as well as power. I-modes have now been maintained in near-DN configurations, leading to improved divertor power flux sharing. Prospects for I-mode on future fusion devices such as ITER and ARC are encouraging. Further experiments on other tokamaks are needed to improve confidence in extrapolation.